Artikel Peningkatan Hasil Tanaman Okra (Abelmoschus esculentus (l.) moench) dengan Pemberian ZPT Auksin dan Pupuk Kandang Ayam - Handayani, Turi; Lubis, Ade Fipriani; Rahmayanti, Sri; Pangaribuan, Mahdar Felayati; Yunita, Della (Jurnal Ilmiah Global Education, 2024)
The study was conducted in the experimental field of the Faculty of Agriculture, Asahan University, Jalan Jendral Ahmad Yani, Kisaran, Asahan Regency from March until May 2021. The study aims to the find out the increase in yield of okra (Abelmoschus esculentus (L.) Moench) by giving auxin and chicken manure. This study used randomized complete block design with two factors: (1) Auxin (Z) with 3 levels: Z0 = 0 ppm, Z1 = 100 ppm, Z2 = 200, (2) Chicken manure (A) with 3 levels: A0 = 0 kg/polybag, A1 = 1 kg/polybag, A2 = 2 kg/polybag. Observation parameters were harvesting age, fruit length, fruit diameter, fruit weight. The result showed that the application of Auxin did not show any significant effect on harvesting age, fruit length, fruit diameter, fruit weight. Application cow manure showed any significant effect on harvesting age, fruit length, fruit diameter, fruit weight, the best treatment is A2 = 2 kg/polybag. Interaction of the application of auxin with chicken manure did not show any significant effect on all observation parameters.